Prevalência e Fatores de Risco Associados ao Sobrepeso e Obesidade em Adolescentes da Cidade de São Luís, Maranhão - Carvalho, Monique Silva Nogueira de (2016)
There is an increase in overweight and obesity prevalence in adolescence, which can be attributed to exposure to modifiable risk factors, and is associated with early onset of disease. The aim of this study was to determine the prevalence of overweight and obesity and its association with possible risk factors in adolescents from a public school in São Luís, Maranhão. This is an analytical and cross-sectional study with adolescents enrolled in public school in São Luís county, aged 10 to 18 years. Data collected involved sociodemographic characteristics (age, sex, skin color, monthly income); exposure to risk factors (family or personal history of disease, eating habits, alcohol use and smoking, physical activity level, age at menarche) and measurements of weight, height, skinfold thickness, waist circumference and neck, blood pressure. For the analysis of the results, it was considered overweight and obesity as overweight. We used SPSS, version 19.0 and were used descriptive analysis and statistical test Chi-square association, as well as multiple regression analysis to assess the association of independent variables on excess weight and abdominal fat. It was considered statistically significant at p <0.05. The prevalence of overweight was 20.5% (43.3% in boys and 56.7% for girls). Sex, consumption of breakfast, blood pressure, parental obesity, waist height and waist circumference were significantly associated with overweight. Excess abdominal fat was significantly associated with sex, age, blood pressure, excess weight, waist height and percentage of body fat. Risk factors associated with excess weight were blood pressure, sex and parental obesity. While age is presented as a risk factor associated with excess abdominal fat. The prevalence of overweight in adolescents students of a state school in São Luís was high, with higher risk of exposure in adolescents with high blood pressure, female and obese parent.